Age-related and training-induced changes in morphological characteristics of young elite male soccer players - Androulakis, N.; Koundourakis, N.; Tsiakiris, C.; Notas, G. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: In soccer, morphological characteristics of young players are particularly important as they have a significant impact on the performance of many technical-tactical elements. Our aim in this study was to investigate whether soccer specific training on its own or combined with strength training can influence the morphological characteristics, of young soccer players and if so, to establish which age is more appropriate for interventions through individualized training. METHODS: The study sample consisted of 61 young male soccer players, members of two under 17 (U171 and U172) and two under 19 (U191 and U192) teams. U171 (N.=17, consists of ages: 15.1±0.6) and U191 (N.=14, consists of ages 17.3±0.5 years) teams performed only soccer specific training whilst U172 (N.=18, consists of ages 15.0±0.4 years) and U192 (N.=12 consists of ages 17.1±0.7 years) teams had two extra strength trainings per week. Anthropometric measurements were performed at the beginning and at the end of the 10- months session. RESULTS: Lean body mass was increased whilst body fat decreased at the end of the study in all teams (P<0.001). No significant changes were found regarding endomorphic and ectomorphic outcome. Mesomorphic outcome was significantly increased only in U172 team (P<0.001). CONCLUSIONS: Our data supports that earlier interventions (between ages 15-17 years) in the training routine may be more effective in order to achieve anatomical and morphological characteristics most favorable for soccer.